IN SEARCH OF THE TRADITIONS IN POLITICAL THINKING: STUDIES OF ENLIGHTENMENT’S POLITICAL THOUGHT IN LITHUANIA - Mačkinis, Vilius (Politologija, 2014)
Despite the fact that Lithuania is lacking the research in the field of the history of its political thought, which would be devoted to the analysis of the Enlightenment, research in the fields of history, history of literature and philosophy are trying to grasp the main contours of the Enlightened age in Lithuanian Grand Duchy. Historical studies are of particular importance, starting with general history of Lithuania and history of Vilnius University. These studies accentuate the reforms influenced by Enlightenment ideas, particularly the educational reform and political ideas presented through the Four Years Sejm and the Constitution of the 3rd May. The special attention to the Enlightenment epoch is paid in the works of Lithuanian historians Eligijus Raila, Vydas Dolinskas, Ramunė Šmigelskytė-Stukienė. Beside historical studies the research into historic literature contribute to the analysis of the Enlightenment as well. These works present historical texts in the context of the Enlightenment. The scholars Sigitas Narbutas and Kristina Mačiulytė from the Institute of Lithuanian Literature and Folklore are the main contributors in this field. The studies in the Enlightenment’s philosophical thought, forming a singular history of the Lithuanian philosophical thinking are found mainly by the scholars from Lithuanian Culture Research Institute. Steponas Tunaitis and Dalius Viliūnas are the scholars working to reconstruct the philosophical tradition in Lithuania.The main research achievement in the field of Enlightenment in general and in its political ideas should not be measured by the amount of publications and wideness of the research, but by the changing view towards the Polish-Lithuanian Commonwealth and importance of its heritage to Lithuania. The revaluation of Four Years Sejm and the Constitution of the 3rd May as integral part of Lithuanian history and part of Lithuanian Enlightenment opens the door to further research into this complex period of history, as well as an opportunity to reconstruct the tradition of Lithuanian political thinking and its influence on the present state of the mind.